1998
DOI: 10.1074/jbc.273.45.29672
|View full text |Cite
|
Sign up to set email alerts
|

Cortactin Associates with the Cell-Cell Junction Protein ZO-1 in both Drosophila and Mouse

Abstract: Cortactin is an actin filament-binding protein localizing at cortical regions of cells and a prominent substrate for Src family protein-tyrosine kinases in response to multiple extracellular stimuli. Human cortactin has been identified as a protein product of a putative oncogene, EMS1. In this report, we describe the identification of a Drosophila homolog of cortactin as a molecule that interacts with Drosophila ZO-1 using yeast twohybrid screening. Drosophila cortactin is a 559-amino acid protein highly expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
118
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(122 citation statements)
references
References 40 publications
4
118
0
Order By: Relevance
“…In the experiment shown in Figure 4A, cortactin protein was immunoprecipitated from UCS15A treated HCT116 cells and the associated ZO1 protein was examined by immunoblot analyses with ZO1 antibody. As reported previously (Katsube et al, 1998), ZO1 associated with cortactin ( Figure 4a, upper panel, lane 2) and could be detected by immunoblotting with ZO1 antibody, which also recognized the 160 kilodalton related protein, ZO2 (Figure 4a, top panel, lanes 1 and 8). Upon UCS15A treatment, the level of cortactin-associated ZO1 diminished in a dose-dependent manner, especially between 2 and 5 mM and was virtually abolished at 10 mM of UCS15A (Figure 4a, upper panel).…”
Section: Ucs15a Is Distinct From Src Kinase Inhibitor Such As Pp2mentioning
confidence: 50%
See 1 more Smart Citation
“…In the experiment shown in Figure 4A, cortactin protein was immunoprecipitated from UCS15A treated HCT116 cells and the associated ZO1 protein was examined by immunoblot analyses with ZO1 antibody. As reported previously (Katsube et al, 1998), ZO1 associated with cortactin ( Figure 4a, upper panel, lane 2) and could be detected by immunoblotting with ZO1 antibody, which also recognized the 160 kilodalton related protein, ZO2 (Figure 4a, top panel, lanes 1 and 8). Upon UCS15A treatment, the level of cortactin-associated ZO1 diminished in a dose-dependent manner, especially between 2 and 5 mM and was virtually abolished at 10 mM of UCS15A (Figure 4a, upper panel).…”
Section: Ucs15a Is Distinct From Src Kinase Inhibitor Such As Pp2mentioning
confidence: 50%
“…To this end, the cortactin ± ZO1 complex, which involves the interaction of an SH3 domain with a typical proline-rich sequence, was chosen as an example of an SH3-mediated interaction that is important in cytoskeletal organization (reviewed in Tsukita et al, 1999). Previous studies have shown that the SH3 domain of the actin-binding protein, cortactin, interacts with a P-x-x-P motif in the prolinerich domain of ZO1 (Katsube et al, 1998). In the experiment shown in Figure 4A, cortactin protein was immunoprecipitated from UCS15A treated HCT116 cells and the associated ZO1 protein was examined by immunoblot analyses with ZO1 antibody.…”
Section: Ucs15a Is Distinct From Src Kinase Inhibitor Such As Pp2mentioning
confidence: 99%
“…The large degree of conservation in the SH3 domain suggests that this domain binds ligands conserved across a broad evolutionary spectrum, performing a similar function(s) in diverse species. The proline-rich segments in invertebrate cortactins are considerably longer than the similar regions in the vertebrate proteins, accounting in part for the low degree of homology (Katsube et al, 1998).…”
Section: Structural Organization Of Cortactin and Related Proteinsmentioning
confidence: 99%
“…Tight junctions are associated with an apical cytoskeletal structure known as the terminal web (Fath et al, 1993). Cortactin is localized at the terminal web in human small bowel epithelium (Wu and Montone, 1998) and the SH3 domain associates with a proline-rich motif in ZO-1 (Katsube et al, 1998), a protein selectively localized to the epithelial tight junction (Stevenson et al, 1986). The ZO-1 proline-rich domain contains a homologous sequence to the consensus cortactin SH3 domainbinding motif (Figure 2d).…”
Section: Function Of Cortactin Sh3-domain Binding Proteinsmentioning
confidence: 99%
See 1 more Smart Citation